Localização de campos em membranas deformadas - Cruz, Wilami Teixeira da (2009)
We analyze the behavior of fields of various ranks in models of extra dimensions and senarios containing membranes with internal structures. For this purpose we start from a five dimensions AdS space-time where the warp factor is defined in terms of a smooth function of the fifth coordinate. The warp factor, as well as the background, are obtained from the deformation of thick brane models. This scenario mimics the Randall-Sundrum scenario (RS), which can be obtained under certain limit. However, the advantage of thick brane models is that they represent a non-singular version of RS (Randall-sundrum) scenarios. Starting from the action with the coupling of a real scalar field and gravity we describe the space-time geometry from the Einstein's equation. Choosing a λφ4 potential, we find kink-like solutions for the scalar field that represents the membrane itself. In this case, the solution interpolates two asymptotically AdS spaces, such as a domain wall. From a deformation procedure of the potential, we obtain a class of brane solutions. The advantage of these new models is that they host internal structures. The solutions also interpolate two AdS spaces with a new transition structure where the scalar field has zero value between the domains. These structures have influence on the scenario's geometry and therefore the localization methods. In this brane scenario we obtained new results on the location of zero modes for the scalar and fermionic fields. Taking the massive modes resulting from the fifth dimension components of the fields, we find new resonance structures. These structures help us to understand the relationship of massive modes with the membrane. New results were also obtained when we take the vector and tensor gauge fields. In such cases, to ensure the location of these fields, we had to introduce a scalar field on the scenario, the Dilaton field. At this point we proceed with a new analysis of the dilaton interaction with the deformed structure. The localization mechanisms of iv gauge and Kalb-Ramond fields are directly affected by the brane's internal structure. Again, analyzing the massive spectrum, we detected significant changes in the potential of the resulting S hroedinger's equation when compared with models of usual branes. Resonance structures are detected in the spectrum for the massive gauge field. Similar structures appear in the study of the Kalb-Ramond field by the two detection methods adopted.